Electrochemical, Spectroscopic, and Computational Investigation of a Series of Polypyridyl Ruthenium(II) Complexes: Characterization of Reduced States - Queyriaux, Nicolas; Esmieu, Charlène; Gupta, Arvind K.; Vendier, Laure; Ott, Sascha; Orio, Maylis; Hammarström, Leif (European journal of inorganic chemistry, 2021)
A series of polypyridyl ruthenium(II) complexes has been synthesized and characterized by 1H‐NMR, electronic absorption and voltammetric techniques. Among this series, hexafluorophosphate salts of eight ruthenium(II) complexes were newly prepared. Due to the well‐known ability of this class of compounds to assist electro‐ and photocatalytic reductive processes (such as the reduction of CO2, H+ and NAD(P)+ models), particular attention has been paid to investigate the nature of their one‐ and two‐electron reduced species through computational and spectroscopic techniques. Identifying key intermediates in catalytic processes involving [Ru(tpy)(bpy)X]‐type complexes is of great importance to understand mechanisms better. We provide a full set of spectroscopic and computational characterizations of the first two reduced states of a series of these complexes.